ML-01 Pathological characteristics of primary central nervous system lymphoma with atypical radiological finding. (28th November 2020) - Inukai, Madoka; Shibahara, Ichiyo; Handa, Hajime; Saruta, Wakiko; Sato, Sumito; Hide, Takuichiro; Kumabe, Toshihiro
Abstract: Background: If the brain tumor is suspected to be a primary central nervous system lymphoma (PCNSL) on radiological findings, it is general to perform biopsy to obtain the pathological diagnosis. Glioblastomas (GBs) must be distinguished from PCNSLs. In addition to commonly used contrast-enhanced T1-weighted imaging, diffusion-weighted image (DWI), and apparent diffusion coefficient (ADC) value, the following characteristics of PCNSLs were reported to be essential for this purpose: 1) no increase in blood flow on perfusion images obtained by the arterial spin labeling (ASL) method; 2) less microbleeding on T2*-weighted images (T2*). However, we experienced some exceptional cases. Purpose: To clarify the histopathological features of PCNSLs those had atypical radiological findings. Method: 62 consecutive PCNSL cases (40 males, 22 females, mean age 65.4 years, range 35–84) treated in our department from April 2013 to March 2020 were retrospectively analyzed. We compared the following features between 47 biopsy cases showing typical image findings as PCNSLs (Group A) and 15 surgically resected cases with atypical findings (Group B), 1) number of blood vessels per hyper 10 fields, 2) occupying area of blood vessels per unit area, 3) immunoreactivity of vascular endothelial growth factor (VEGF), and 4) germinal center B-cell (GCB) subtype. Results: In Group A, the number of blood vessels in the tumor was 39.3 on average, and the area occupied by blood vessels was 3.8%. In Group B, the former was 133.2, and the latter was 9.9%. There was no significant difference in VEGF expression and GCB subtype. Conclusion: In PCNSLs showing with high blood flow and microbleeds, the blood vessels were rich and partial bleeding was confirmed histologically. We should analyze much more cases to set the threshold both of the ADC value and the absolute value of blood flow calculated by the ASL method to distinguish between PCNSLs and GBs.